Variable Charge of Ultisols due to Phosphate Application and Incubation Time - Muhammad Mahbub (UNIVERSITY OF LAMPUNG, 2010)
Variable Charge Ultisols due to Phosphate Application and Incubation Time (M Mahbub): The laboratory experiment was conducted to study the effect of phosphate (P) application and its incubation time on pHo (pH at the point of zero charge) and variable charge of ultisols . The determined parameters were pHo and variable surface-charges. Soil samples were added by 0, 375 and 1,125 mg P kg-1 (or 0, 50 and 150% of the P sorption maximum, respectively). Then, they were incubated for 2, 4, 6 and 8 weeks. The variable surface-charges and pHo were determined by using the activity of potential determining ions (H+ and OH-) within two salt concentrations as counter ions (0.1N and 0.001N CaCl2) through a potentiometric titration method. The results were indicated that the high P sorption and 766 mg P kg-1 in maximum sorption were due to high contents in clay fractions and aluminum as well as low pH of experimental soil. Application of P and incubation time were able to decrease pHo and to increase negative surface-charges. Additionals of 375 and 1,125 mg P kg-1 incubated for 8 weeks gave the value of pHo 2.86 and 2.69; as well as the magnitude of negative charges 14.48 and 16.76 cmol(-).kg-1, respectively (both for 0.001N CaCl2). For pH > pHo (the characteristic of variable charge soils), the higher the salt (CaCl2) concentration and pH solution, the higher the negative surface-charge.